Domestic or U.S. news: what drives Canadian financial markets? - Bernd Hayo; Matthias Neuenkirch (Philipps-University Marburg, Faculty of Business Administration and Economics, 2009)
Using a GARCH model, we study the effects of Canadian and U.S. central bank communication and macroeconomic news on Canadian bond, stock, and foreign exchange market returns and volatility. First, news in both categories and from both countries has an impact on all financial markets. Canadian and U.S. price shocks and monetary policy news are less important than shocks relating to the real economy. Second, Canadian central bank communication is more relevant than its U.S. counterpart, whereas in the case of macro news that originating from the United States dominates. Third, we find evidence that the impact of Canadian news reaches its maximum when the Canadian target rate departs from the Federal Funds target rate (2002–2004). The introduction of fixed announcement dates (FAD) does not cause a noticeable break in the data. Finally, Canadian and U.S. target rate changes lead to higher price volatility, and so does other U.S. news. Other Canadian news, however, lowers price volatility.
Keywords: E52; G14; G15; 330; Bank of Canada; Central Bank Communication; Federal Reserve Bank; Financial Markets; Macroeconomic News; Monetary Policy